Pembentukan Kecerdasan Emosional Melalui Kegiatan Keagamaan di MTs Ihya’ul Ulum Dukun Gresik: Penelitian - Anfa Regita Ayu Pratiwi; Muh. Sabilar Rosyad (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the development of students’ emotional intelligence through religious activities at MTs Ihya’ul Ulum Dukun Gresik. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings reveal that structured religious activities such as performing sholat dhuha and dhuhur in congregation, reciting prayers before lessons, and reading the Qur'an regularly significantly contribute to building student discipline, inner peace, and emotional self-control. Supporting factors include the active involvement of the school, teachers, parents, and a conducive social environment. Meanwhile, inhibiting factors include lack of parental attention, low student motivation, unsupportive external environments, and technical challenges such as weather conditions. The study concludes that consistent and well-structured religious activities are effective in fostering students’ emotional intelligence holistically.